A solid-state NMR and X-ray powder diffraction investigation of the binding mechanism for self-healing cementitious materials design: The assessment of the reactivity of sodium silicate based systems. (February 2017) - Irico, S.; Bovio, A.G.; Paul, G.; Boccaleri, E.; Gastaldi, D.; Marchese, L.; Buzzi, L.; Canonico, F.
Abstract: The identification of affordable healing agents for cement based materials, able to promote autonomous crack healing, is a challenge to improve the durability of building structures. In this study, a thorough investigation of the reactivity between a hydrated Portland cement and sodium silicate solutions, as healing agents, has been carried out. The goal is to quantitatively assess the chemical reactivity and actual binding capacity of sodium silicate. Mechanical recovery was evaluated by means of a healing agent strength test on hydrated cement treated with sodium silicate. XRPD and Solid-state NMR allowed the definition of reaction times, the involved species, and the nature and stability of the reaction products. Highlights show that sodium silicate reacts not only with Ca(OH)2 (namely portlandite), but also with calcium aluminate phases (AFt, AFm, TAH) to extract calcium and/or aluminum ions, with the formation of crystalline/semi-crystalline C-S-H/C-A-S-H tobermorite phase.